STUDI NUMERIK TURBIN ANGIN SAVONIUS: TORSI MEKANIK, DIAMETER POROS, DAN DAYA - Filian Arbiyani; Fernando Pranata Lasut; Fransiskus Albert (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
One of the renewable energy sources that can be used to generate electricity is wind energy. This research aims to numerically study the Savonius Vertical Axis Wind Turbine (VAWT) type to obtain the mechanical torque, load torque, shaft diameter, and the empirical equation showing the relationship between the mechanical torque and power generated. The numerical study employs MATLAB R2018a software with the parameters mechanical torque, load torque, and power. The obtained mechanical torque is also used to determine the design of the shaft diameter based on its maximum mechanical torque. From this numerical study, the value of mechanical torque is greater than the mechanical load, and it also obtains the empirical equation of the relationship between mechanical torque and power. Validation is carried out on the empirical equation with valid results as it has the Â± 10% tolerance.Â Furthermore, it is obtained that the design of the minimum shaft diameter of the wind turbine with PLA (Polylactic Acid) filament material is 2 mm. This Savonius turbine design can be used for placement on vehicles and in areas in Indonesia with low to high wind speeds with variations between 1 m/s â€“ 17 m/s.